Correlation of the Faraday and Kerr Magneto-Optical Effects in Transmission-Line Terms - Luhrs, C. H. (Proceedings of the IRE, 1952)
The subject effects follow immediately from the assumption of the inequality of the two sets of Maxwell's material constants, one set for right-handed circularly polarized waves and and the other for left-handed circularly polarized waves. The Faraday magneto-optical effect is derived from phase considerations, and the Kerr magneto-optical effect is derived from impedance considerations.